The Effect of Company’s Performance on Tax Avoidance - Lilis Renfiana; Sevrina Candra Dewi (Journal of Business and Management Review, 2020)
Researchers want to examine tax avoidance that occurs in companies listed in LQ45. As is well known, the LQ45 index represents 45 companies that have gone through a selection process with high liquidity (Liquid) and considerations of large market capitalization. Companies that are listed in LQ45 are very interesting to research, which companies that go public and liquid are doing Tax Avoidance or tax avoidance. Tax avoidance variables use CETR or ( Cash Effective Tax Rate) and company performance variables use ROA (Return on Asset). Analyzed by quantitative, secondary data obtained from the financial statements of companies that consistently included in the LQ45 index in the year 2014 to 2018 on the website Stock Exchange Indonesia, namely www.idx.co.id . The number of samples obtained were 21 companies. The data analysis technique used simple regression with the SPSS application. The results showed that company performance did not affect tax avoidance attitudes. companies listed on LQ45 are still compliant with tax payments in accordance with the portion